The impact of resiliency on mental health and quality of life among older adults in Thailand - Paul Ratanasiripong; Nop Ratanasiripong; Monpanee Khamwong; Sarinya Jingmark; Ploenpit Thaniwattananon; Pennapa Pisaipan; Ladda Sanseeha; Nongnaphat Rungnoei; Wallapa Songprakun; Asawinee Tonkuriman; Suchart Bunyapakorn (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - The aim of this study was to examine the impact of resiliency and associated factors on the mental health and quality of life among older adults in Thailand. Design/methodology/approach - This cross-sectional study was conducted with 1,800 older adults (M = 69.3, SD = 7.2) from nine provinces across all regions of Thailand. Each participant completed an anonymous paper-based survey that included demographic data, work activities, health behaviors, social support, Connor-Davidson Resilience Scale (CD-RISC), Depression, Anxiety, Stress Scale (DASS) and World Health Organization Quality of Life Assessment for Older Adults (WHOQOL-OLD). Findings - Through hierarchical multiple regression, resiliency, social support, exercise and work hours per week were found to be significant predictors of mental health: depression (F (6, 520) = 19.38, p < 0.001, adjusted R2 = 0.17); anxiety (F (6, 520) = 18.64, p < 0.001, adjusted R2 = 0.17); stress (F (6, 521) = 12.91, p < .001, adjusted R2 = 0.12). Five predictors of quality of life were identified through hierarchical multiple regression: resiliency, social support, exercise, age and family economic status. These predictors explained 35% of the variance, F (5, 1655) = 178.44, p < 0.001, adjusted R2 = 0.35. Originality/value - Based on the results of this study, a comprehensive Wellness Program was designed to improve the mental health and quality of life of older adults in Thailand. This Wellness Program included five components: Volunteer Program, Resiliency Building Program, Social Support Program, Exercise Program, and Financial Education Program.